PENINGKATAN KEMAMPUAN KOGNITIF MELALUI PERMAINAN MENCARI URUTAN LAMBANG BILANGAN PADA ANAK USIA 5-6 TAHUN - (F54210041), Nurmalasari; ., Marmawi; ., Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
This research is a form of action research with descriptive methods . Subjects were 1 teacher and children , amounting to 15 children . Based on the research that has been done and through the results obtained after an analysis of data that : 1 ) Planning for meningatkan learning cognitive skills through the game looking for a symbol sequence numbers 1-10 in children can be categorized as " excellent " , while the teachers' planning has been done include: formulating learning goals , choosing a theme , selecting play materials , teaching methods , assessing learning outcomes . 2 ) Implementation of learning to improve skills through the game looking for a symbol sequence numbers 1-10 in children can be categorized as " excellent " , while the implementation has been done , among others : the teacher pre- learning activity , the teacher opened the lesson , the teacher core activities of learning , teacher close the learning . 3 ) Improvement of cognitive abilities through the game looking for a symbol sequence numbers 1-10 in children can be categorized as " developed in line with expectations " with activities including: a) the child can sort the symbol numbers 1-10. b ) children 1-10 numbers mentioned symbol. c ) and connecting the child match numbers with symbol numbers 1-10 . Keywords: Cognitive, Games Looking Sequence Numbers Symbol Abstrak: Bentuk penelitian ini adalah penelitian tindakan kelas dengan metode deskriptif. Subjek penelitian adalah guru 1 orang dan anak yang berjumlah 15 anak. Berdasarkan hasil penelitian yang telah di lakukan dan melalui hasil yang diperoleh setelah diadakan analisis data bahwa: 1) Perencanaan pembelajaran untuk meningatkan kemampuan kognitif melalui permainan mencari urutan lambang bilangan 1-10 pada anak dapat dikategorikan baik sekali, adapun perencanaan yang telah dilakukan guru antara lain: merumuskan tujuan pembelajaran, memilih tema, memilih bahan main, menggunakan metode pembelajaran, menilai hasil belajar. 2) Pelaksanaan pembelajaran untuk meningkatkan kemampuan melalui permainan mencari urutan lambang bilangan 1-10 pada anak dapat dikategorikan baik sekali,adapun pelaksanaan yang telah dilakukan antara lain: guru melakukan kegiatan pra pembelajaran, guru membuka pembelajaran, guru melakukan kegiatan inti pembelajaran, guru menutup pembelajaran. 3) Peningkatan kemampuan kognitif melalui permainan mencari urutan lambang bilangan 1-10 pada anak dapat dikategorikan berkembang sesuai dengan harapan dengan kegiatan antara lain: a) anak dapat mengurutkan lambang bilangan 1-10 b) anak menyebutkan lambang bilangan 1-10 c) anak mencocokkan dan menghubungkan bilangan dengan lambang bilangan 1-10. Kata Kunci : Kognitif, Permainan Mencari Urutan Lambang Bilangan